(untitled) (Research, Society and Development, 2021)
The objective was to describe the scientific evidence about nursing care aimed at preterm newborns. An integrative literature review study was carried out. To search for data, collection sources were used in online research platforms, the Virtual Health Library (VHL) in the following databases: Medical Literature Analysis and Retrieval System Online (MEDLINE), Latin American and Caribbean Literature in Sciences of the Health (LILACS) and Database in Nursing (BDENF) from 2016 to 2021. The descriptors “Nursing Assistance” were used; “Premature newborn”, “Neonatal Nursing”. 1,075 were selected, soon after the inclusion criteria were applied and 159 articles were selected for reading of titles and abstracts. Then, 12 articles that met the research objectives were selected to compose the study. The study results showed that the year of greatest publication was 2019, with a qualitative approach prevailing with 75% of the selected studies, and from the analyzed articles, two categories emerged for the discussion of the theme: Nursing care in the care of pre-born newborns. -term and Knowledge of the Nurse about the care of the preterm newborn. It was concluded that nursing care for preterm newborns is essential because they need specialized care due to clinical conditions, they need an appropriate environment, with adequate technological and human resources, to ensure the treatment and restoration of their health.